2023
DOI: 10.1200/jco.2023.41.17_suppl.lba6002
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 blockade with sintilimab plus induction chemotherapy and concurrent chemoradiotherapy (IC-CCRT) versus IC-CCRT in locoregionally-advanced nasopharyngeal carcinoma (LANPC): A multicenter, phase 3, randomized controlled trial (CONTINUUM).

Abstract: LBA6002 Background: Despite the success of PD-1 blockade plus chemotherapy in recurrent/metastatic NPC, its role in LANPC is unproven. This trial evaluated the efficacy and safety of adding sintilimab (a PD-1 inhibitor) to IC-CCRT in LANPC. Methods: Patients with non-metastatic high-risk LANPC (stage III-IVA, excluding T3-4N0/T3N1) were enrolled at 9 centers in China, and randomized (1:1; stratified by center and stage with block size four) to the Standard Arm (gemcitabine and cisplatin IC plus cisplatin CCRT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Therefore, initiating PD-1 inhibitor treatment before radiotherapy may better activate the immune system and enhance the efficacy of immunotherapy. For LANPC patients, initial findings from the CONTINUUM study suggested that the use of Sintilimab (PD-1 inhibitor) in combination with IC, CCRT, and adjuvant therapy significantly improves the 3-year event-free survival rate compared to those treated with IC plus CCRT (86.1% vs. 76.0%) ( 22 ). In our study, we found short-term survival was excellent by using IC and PD-1 inhibitor with a median follow-up time of 17.0 months.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, initiating PD-1 inhibitor treatment before radiotherapy may better activate the immune system and enhance the efficacy of immunotherapy. For LANPC patients, initial findings from the CONTINUUM study suggested that the use of Sintilimab (PD-1 inhibitor) in combination with IC, CCRT, and adjuvant therapy significantly improves the 3-year event-free survival rate compared to those treated with IC plus CCRT (86.1% vs. 76.0%) ( 22 ). In our study, we found short-term survival was excellent by using IC and PD-1 inhibitor with a median follow-up time of 17.0 months.…”
Section: Discussionmentioning
confidence: 99%
“…Phase II single-arm trials for pembrolizumab [127] and tislelizumab [128] (both PD-1 inhibitors) have studied the efficacy of integrating PD-1 inhibitors with IC and CCRT, followed by maintenance therapy, with results presented in abstract form. The phase III CONTINUUM [129] study recruited patients with stage III-IVA NPC (except T3/T4N0 or T3N1). The experimental arm received up to 12 cycles of induction, concurrent and maintenance sintilimab (a PD-1 inhibitor), and it demonstrated improved 3-year event-free survival compared to the control arm treated with IC +CCRT (86.1% vs. 76%; stratified HR 0.59).…”
Section: Rt In the Era Of Immunotherapymentioning
confidence: 99%
“…The CONTINUUM [129] study proposed that the clinical benefit of sintilimab was observed only in patients with tertiary lymphoid structure (TLS), the ectopic lymphoid tissues that can be found in the tumor or neighboring peripheral tissue [132]. Genomic studies on the tumor microenvironment may offer further insights [124,133].…”
Section: Rt In the Era Of Immunotherapymentioning
confidence: 99%
“… 125 , 126 , 127 , 128 The only large-scale, phase III trial with published data thus far investigating PD-1 blockade in treating locoregionally advanced NPC demonstrated that adding sintilimab during GP IC, CCRT, and as adjuvant therapy significantly lowered recurrence or mortality risk by 41% in high-risk patients—with the 3-year event-free survival rate increasing by 10% (86.1% vs. 76.0%; HR 0.59, 95% CI 0.38–0.92; p = 0.019; Table S1 ). 129 Moreover, the sintilimab group demonstrated significant reductions in distant metastasis and locoregional recurrence risks (3-year DMFS rate, 90.3% vs. 82.8%, HR 0.57 [95% CI 0.33–0.98], p = 0.039; 3-year LR-FFS rate, 93.4% vs. 86.8%, HR 0.52 [95% CI 0.27–0.97], p = 0.038). Notably, no significant difference was observed in the quality of life between the groups.…”
Section: Boosting Efficacy Further: the Evolving Field Of Immunothera...mentioning
confidence: 99%